Antioxidant and hepatoprotective effects of Artemisia dracunculus against CCl4-induced hepatotoxicity in rats - Vahid Zarezade; Jalal Moludi; Mostafa Mostafazadeh; Mohammad Mohammadi; Ali Veisi (Avicenna Journal of Phytomedicine, 2017)
Objective: The present study was conducted to investigate the antioxidant and hepatoprotective activity of the hydro-alcoholic extract of aerial parts of Artemisia dracunculus (HAAD) against CCl4-induced hepatotoxicity in rats. Materials and Methods: The antioxidant activity was evaluated by reducing power, 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 20-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays. Rats were pre-treated with either 50, 100, and 200 mg/kg of HAAD or silymarin (100 mg/kg; served as the positive control group) for 15 days and they received a single dose of CCl4 on the last day. Hepatoprotective effects were investigated by assessment of serum biochemical enzymes such as alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), total protein (TP), total bilirubin (TB), malondialdehyde (MDA), and antioxidant enzymes (SOD, CAT, GST and GSH), along with histopathological studies. Results: Total phenolic content was 197.22±3.73 mg gallic acid equivalent/g HAAD dry weight. HAAD indicated powerful activity in FRAP, DPPH and ABTS tests. Acute toxicity study showed that the extract had an LD50 of >5000 mg/kg. Oral treatment with HAAD exhibited a significant decrease in the levels of AST, ALT, ALP and TB and an increase in the level of TP. The extract significantly diminished MDA levels. The activities of the antioxidant enzymes were significantly augmented in rats pretreated with HAAD 200 mg/kg. Histopathological examination demonstrated lower liver damage in HAAD-treated groups as compared to CCl4 groups. Conclusion: Our findings indicated hepatoprotective effects of the hydro-alcoholic extract of A. dracunculus on CCl4-induced hepatic damage in rats and suggested that these effects may be produced by reducing oxidative stress.